Profil Kecepatan Bicara pada Siswa Kelas 1 SD di Kota Surakarta - Elza Dinda Angelina; Arif Siswanto; Anisyah Dewi Syah Fitri (Politeknik Kesehatan Kemenkes Surakarta, 2026)
Background: Speech rate has a significant impact in an individual’s communication ability and speech fluency in daily interactions. This aspect requires early attention, especially during the initial years of elementary education, which are known as a period of rapid development in children’s abilities.Objectives: to discover speech rate profile of first-grade elementary school students in Surakarta City and to escertain normative standards for speech rate. Methods: This study adopted a descriptive quantitative approach with a cross-sectional research design and univariate analysis. A total of 103 first-grade elementary school students participated from five districts in Surakarta City. Participants were selected according to established inclusion and exclusion criteria. Results: The results showed that the speech rate of first-grade students ranged between 35 and 118 words per minute and 73 to 267 syllables per minute. The average speech rate was 63 words per minute and 135 syllables per minute. Conclusion: Speech rate of first-grade elementary school students in Surakarta City falls into the moderate or normal category. Therefore, this study can provide preliminary information on first-grade students’ speech rates, which can support speech therapists in identifying and evaluating children’s speech issues, particularly those related to speech fluency, as well as in developing appropriate therapy program plans. Keywords : Speech Rate, First-Grade Students, Elementary School, Standard Norms.